The Application of Dwangsom in The Execution of State Administrative Court Decisions in Indonesia From A Justice Perspective - Effendi; Ardiansyah; Libra, Robert (PT Mattawang Mediatama Solution, 2025)
Article 116 paragraph (4) of Law Number 51 of 2009 stipulates that officials who do not implement decisions of the State Administrative Court (PTUN) that have permanent legal force may be subject to coercive measures in the form of forced money (dwangsom) and/or administrative sanctions. This study aims to: first, analyze the legal regulations on dwangsom in the execution of PTUN decisions in Indonesia; second, examine the application of dwangsom by judges in judicial practice; third, examine the implications of the application of dwangsom from a justice perspective. The method used is normative juridical with a statutory, conceptual, and case approach. Data were obtained from primary and secondary legal materials, analyzed qualitatively, with a case study on Decision Number 13/G/2016/PTUN.TPI. The results of the study indicate that the regulation of dwangsom in the execution of PTUN decisions is still partial and not supported by technical regulations. Article 116 paragraph (4) of Law Number 51 of 2009 is not accompanied by detailed guidelines so that its application depends on the judge's initiative and the plaintiff's request, without quantitative or procedural standards. In fact, dwangsom has the potential to be an effective means of pressuring officials to comply with decisions voluntarily and in a timely manner. Weak technical regulations and an unresponsive legal culture have limited its effectiveness. The conclusion of this study confirms that the dwangsom plays a strategic role in ensuring legal certainty and protecting the public's rights from arbitrary government action. Comprehensive technical regulations and the establishment of an independent national enforcement agency are recommended to ensure the practical implementation of PTUN decisions. Thus, dwangsom can function effectively as an instrument for upholding the rule of law and providing justice for those seeking justice.